Constructing Adaptive Photosensitizers via Supramolecular Modification Based on Pillararene Host–Guest Interactions. (12th May 2020) - Shao, Li; Pan, Yutong; Hua, Bin; Xu, Shidang; Yu, Guocan; Wang, Mengbin; Liu, Bin; Huang, Feihe
Abstract: In order to promote the development of photodynamic therapy (PDT), undesired side effects like low tumor specificity and the "always‐on" phenomenon should be avoided. An effective solution is to construct an adaptive photosensitizer that can be activated to generate reactive oxygen species (ROS) in the tumor microenvironment. Herein, we design and synthesize a supramolecular switch based on a host–guest complex containing a water‐soluble pillar[5]arene (WP5 ) and an AIEgen photosensitizer (G ). The formation of the host–guest complex WP5 ⊃G quenches the fluorescence and inhibits ROS generation of G . Benefitting from the pH‐responsiveness of WP5, the binding site between G and WP5 changes in an acidic environment through a shuttle movement. Consequently, fluorescence and ROS generation of the host–guest complex can be switched on at pH 5.0. This work offers a new paradigm for the construction of adaptive photosensitizers by using a supramolecular method. Abstract : A supramolecular switch based on a host–guest complex containing a water‐soluble pillar[5]arene and an AIEgen photosensitizer was fabricated. Fluorescence and ROS generation of this switch can be switched on at pH 5.0. This work offers a new paradigm for the construction of adaptive photosensitizers based on supramolecular chemistry.